Estrada de ferro Belém-Bragança: sujeitos, memórias e narrativas na Amazônia paraense - COSTA, Vânia Maria Torres (Associação Nacional dos Programas de Pós-Graduação em Comunicação, 2022)
This article problematizes the meanings and interactions of social subjects, following the route of the former Belém-Bragança Railroad (EFB), deactivated by the military government in 1965. The train, as a means of communication, instigates us to reflect on the relations, clusters and cities that have emerged from their travels and displacements, as well as the family nuclei that formed near the railroad. The memorable narratives about this railroad will serve as an initial symbolic map to problematize the relations between communication, culture and identities in the paraense Amazon. Books, photos, maps, blogs and videos are clues to search for traces of the Bragança train and its passengers through their narratives. One can perceive how these texts produce in time the totality of this experience that has crossed lives in times dated as an event remembered in search of self-construction from the collective memory.